Profiles of Social-Emotional Readiness for 4-Year-Old Kindergarten - Miller, Michele M.; Goldsmith, H. Hill (Frontiers in Psychology, 2017)
Children who are viewed as ready for kindergarten and/or first grade typically exhibit high attention, approach, and adaptability coupled with low activity and reactivity. These characteristics tend to be especially valued by teachers and describe a child who is “teachable,” or school ready. Since many children enter formal schooling earlier by attending pre-K for 4-year olds, often called 4-year-old kindergarten, there is a need to examine school readiness earlier than kindergarten, which may look very different developmentally. If we expect children to enter formal schooling at age 4, then it should be clear what we expect of them in order to succeed. We explored which temperament, behavior, and cognitive items teachers of 4-year-old kindergarten (N = 29) rated as highly characteristic versus uncharacteristic of ready 4-year-olds. This teacher-generated data identified five clusters of children who were deemed ready for 4-year-old kindergarten. Teachers noted high cognitive skills and following directions as salient in many of the clusters, which aligns with the readiness expectations for kindergarten and first grade. However, items that distinguished the five clusters from one another referenced differences in activity level, sociability, shyness, enthusiasm, and patience that were not expected based on the previous literature with slightly older children. Given that some of the children teachers identified as especially ready for 4-year-old kindergarten did not fit this static model of a “teachable” child, a single profile of school readiness at an early age may be inappropriate.